Taqwīmu Ta’līm Al-Lughah Al-‘Arabiyyah ‘inda Imām Zarkasyi wa Imām Syubbāni fī Kitāb Al-Tamrīnāt - Rizza Faesal Awaludin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2020)
The evaluation book has been made a lot during this time, and one of the books that is carried out in the evaluation in teaching Arabic is the book “At Tamrinaat” as an application of the book “Durūsul Lughah Al Arabiyyah” written by KH. Imam Zarkasyi and Imam Syubani. Teaching Arabic in the words of KH. Imam Zarkasyi and Imam Syubani is in the book "At Tamrinaat". This research is a desk study on the idea of KH. Imam Zarkasyi and Imam Syubani in teaching the Arabic language which is visualized in the book " At Tamrinaat ". To collect data, the researcher used the curriculum of written documents, which means requesting data on things and the variable in the forms of writing, text, books, and the newspaper. Comprehensive descriptive document research was used to analyze the data. The result of this research is that the evaluation of materials in this book used the direct method, by presenting first the example and then taking the result. The goals of this book for learners in teaching the Arabic language are to have a comprehensive ability to speak the Arabic language with the best pronunciation, soundness of rules, and a good understanding and perception therein. With this method of evaluation, which depends on the foundations of continuity, it gives a great experience to learners, as it improves their understanding of the Arabic language.